The Trash Attack: An Attack on Verifiable Voting Systems and a Simple Mitigation - Benaloh, Josh; Lazarus, Eric (Microsoft Technical Report, 2011)
This short paper describes the trash attack which is effective against the majority of fully-verifiable election systems. The paper then offers a simple but counter-intuitive mitigation which can be incorporated within many such schemes to substantially reduce the effectiveness of the attack. This mitigation also offers additional benefits as it significantly improves the statistical properties of existing verifiable systems.